Following the Frankincense Reassessing the Sitz im Leben of Targum Song of Songs - Litke, Andrew W. (2018)
It is commonly asserted that Targum Song of Songs was composed in Palestine in the seventh or eighth century CE. This article surveys the most significant criteria used to posit that assertion (such as language, Jewish education, and messianism), and it argues that these criteria are either inconclusive or point to a different Sitz im Leben for the Targum. The article then adds one element to the discussion, the use of the late Latin term olibanum, 'frankincense', in 4.11. Ultimately, this article argues that the traditional dating and provenance of Targum Song of Songs' composition should be adjusted. A tenth- or eleventh-century time period and a location in either southern Italy or Byzantium better fit the evidence.
Keywords: Jewish education; Late Jewish Literary Aramaic; Sitz im Leben; Targum; Targum Song of Songs; Messianism; olibanum